Rapid CO gas dispersal from NO Lup's class III circumstellar disc. Issue 1 (30th November 2020) - Lovell, J B; Kennedy, G M; Marino, S; Wyatt, M C; Ansdell, M; Kama, M; Manara, C F; Matrà, L; Rosotti, G; Tazzari, M; Testi, L; Williams, J P
ABSTRACT: We observed the K7 class III star NO Lup in an ALMA survey of the 1–3 Myr Lupus association and detected circumstellar dust and CO gas. Here we show that the J = 3–2 CO emission is both spectrally and spatially resolved, with a broad velocity width ∼19 km s −1 for its resolved size ∼1 arcsec (∼130 au). We model the gas emission as a Keplerian disc, finding consistency, but only with a central mass of ∼11M⊙, which is implausible given its spectral type and X-Shooter spectrum. A good fit to the data can also be found by modelling the CO emission as outflowing gas with a radial velocity ∼22 km s −1 . We interpret NO Lup's CO emission as the first imaged class III circumstellar disc with outflowing gas. We conclude that the CO is continually replenished, but cannot say if this is from the breakup of icy planetesimals or from the last remnants of the protoplanetary disc. We suggest further work to explore the origin of this CO, and its higher than expected velocity in comparison to photoevaporative models.